2016
DOI: 10.1002/0471140856.tx1413s67
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Induced Pluripotent Stem Cells for the Study and Treatment of Liver Diseases

Abstract: Liver disease is a major global health concern. Liver cirrhosis is one of the leading causes of death in the world and currently the only therapeutic option for end-stage liver disease (e.g., acute liver failure, cirrhosis, chronic hepatitis, cholestatic diseases, metabolic diseases, and malignant neoplasms) is orthotropic liver transplantation. Transplantation of hepatocytes has been proposed and used as an alternative to whole organ transplant to stabilize and prolong the lives of patients in some clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 184 publications
0
19
0
Order By: Relevance
“…Rapidly developing iPSC technologies provide an unprecedented opportunity for researchers and clinicians [ 344 ]. Recent studies have shown that iPSC-derived hepatocytes can be used for the investigation of the genetic and molecular mechanisms of liver disorders [ 240 , 242 , 244 , 345 356 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly developing iPSC technologies provide an unprecedented opportunity for researchers and clinicians [ 344 ]. Recent studies have shown that iPSC-derived hepatocytes can be used for the investigation of the genetic and molecular mechanisms of liver disorders [ 240 , 242 , 244 , 345 356 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that liver disease is a major health concern worldwide ( 38 ). Statistics published in 2014 estimated that the number of new liver cancer cases in the USA totaled 33,190 (24,600 male cases), and the estimated mortality rate was 23,000 (15,870 male cases).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes have been transplanted into the liver, spleen, and peritoneal cavity, with intraportal injection being the preferred and most physiological site for clinical transplantation[ 14 , 42 ]. This site may be accessed via percutaneous trans-hepatic puncture, cannulation of the umbilical vein, or open cannulation of a mesenteric vein[ 14 ].…”
Section: Methods Of Deliverymentioning
confidence: 99%
“…Alpha 1 antitrypsin (A1AT) deficiency - in 1997, a 52 years old patient underwent HTx as a bridge to transplant, with wild type A1AT levels were noted to increase in the interval between OLT, which occurred 2 d later[ 42 ].…”
Section: Clinical Indications For Hepatocyte Transplantationmentioning
confidence: 99%